Avaliação dos efeitos do eugenol e do óleo essencial de Ocimum gratissimum durante o cultivo in vitro de folículos pré-antrais bovinos - Vasconcelos, Erlândia Márcia (2020)
The aim of this work was to evaluate the effects of different concentrations of Eugenol and the essential oil of Ocimum gratissimum on growth, viability, morphology, antrum formation and mRNA expression for SOD, CAT, GPX1, and PRDX6 in secondary bovine follicles grown in vitro. Bovine ovaries were collected in a local slaughterhouse, under aseptic conditions. In the laboratory, the secondary follicles were isolated from the ovarian cortex and cultured in TCM- 199 + drops alone or supplemented with different concentrations of the essential oil of Ocimum gratissimum (0.125%, 0.25% and 0.5%) and Eugenol (5, 10 and 50 μM). The culture medium was changed every 2 days and the photographic record of the follicles was done on days 0, 6, 12 and 18, with growth rate and antrum formation being observed. At the end of the cultivation period, the follicles were subjected to viability analysis using calcein (viable) and homodimer ethidium (non-viable). In addition, follicles were used to quantify messenger RNA levels for SOD, CAT, GPX1 and PRDX6. The data on follicular growth were submitted to ANOVA, followed by the T test. For the analysis of follicular viability and antrum formation, the Chisquare test was used (p <0.05). The messenger RNA expression data were analyzed using the nonparametric Kruskal-Wallis test (p <0.05). The results showed that the secondary follicles grown in the presence of the essential oil of O. gratissiumum maintained morphology, viability and growth. In addition, the presence of 0.5% or 0.25% essential oil in the culture medium significantly increased the levels of mRNAs for PRDX6 and CAT. Secondary follicles grown with Eugenol maintained similar morphology and viability to the control group. A progressive increase in follicular diameter was observed between days 0 and 12 in all treatments, except for follicles grown with 50 μM Eugenol. 5.0 and 50.0 μΜ Eugenol increased mRNA levels for PRDX6 in follicles, but 0.5 μΜ Eugenol reduced mRNA levels for SOD in cultured follicles. Eugenol did not influence mRNA expression for CAT and GPX1. In conclusion, O. gratissimum essential oil increases the levels of mRNAs for PRDX6 and CAT in secondary bovine follicles grown in vitro for 18 days and maintains their viability, morphology and growth. Eugenol reduces the levels of mRNAs for SOD and increases the levels of PRDX6 in bovine secondary follicles grown in vitro. Eugenol maintains follicular viability and morphology, but reduces follicular growth when in high concentration (50 μM).